Deliberation and decisions in the IRB process - Nancy Neveloff Dubler (Social Medicine Publication Group, 2013)
Institutional review boards (IRBs) regularly vote to resolve conflict. This article argues that voting minimizes protections for human subjects and violates moral order. Rather than vote, IRBs should be mediating disputes, which respects the moral difference and integrity of IRB members.